ANALISIS PENGARUH CUSTOMER SATISFACTION DAN TRUST IN BRAN TERHADAP CUSTOMER RETENTION (Studi Kasus Pengguna Kartu XL di Sekolah Tinggi Manajemen Labora) - Sumarsid Sumarsid; Atik Budi Paryanti (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThis study aims to determine several factors that can affect customer retention, including customer satisfaction and trust in brand. Therefore, it is necessary to know how the company, in this case XL as the object of research, applies these factors in order to increase customer retention of XL card users, either partially or simultaneously. The type of research used is research with a quantitative descriptive approach. This research uses samples of 31 XL card users at Labora Management College. Based on the hypothesis test with the t test, it was found that a significant value of Customer Satisfaction was 0.142> 5% (0.142> 0.05), thus to> tα then Ha (alternative hypothesis) was rejected and Ho (hypothesis nil) was accepted. This means that partially Customer Satisfaction has no significant effect on Customer Retention of XL card users at Labora Management College. Likewise, the significant value for the X2 Trust In Brand variable is 0.169> 5% (0.169> 0.05), thus to> tα, then Ha (alternative hypothesis) is rejected and Ho (null hypothesis) is accepted. This means that the X2 Trust In Brand variable partially does not have a significant effect on Customer Retention of XL card users at Labora Management College Based on the hypothesis test with the F test, it is found that the significant value of F is 0.007, meaning <5%, (0.007 <0.05) thus Ho is rejected and Ha is accepted so that it can be concluded that simultaneously Customer Satisfaction and Trust In Brand have a significant effect on Customer Retention of XL card users. at Labora College of Management. Based on the results of multiple linear regression analysis, the equation Y = 4.365 + 0.157 X1 + 0.262 X2 means that if the Customer Satisfaction value is increased by 1 point / unit, then Customer Retention (Y) will increase by 0.157 points / unit, while each increase in Trust In Brand the value is increased. 1 point / unit, then Customer Retention (Y) will increase by 0.262 points / unit Keywords: Customer Satisfaction, Trust In Brand and Customer Retention